Analysis of Factors Affecting Gross Regional Domestic Product (GRDP) in Bali Province - Ni Nyoman Widiani; Surya Dewi Rustariyuni (International Journal of Economics, Management and Accounting, 2025)
Bali Province is a world-renowned tourism destination that significantly contributes to the Gross Regional Domestic Product (GRDP) of the region. However, the COVID-19 pandemic led to a severe economic downturn, causing negative economic growth. This study aims to examine the simultaneous and partial effects of tourist visits, local revenue (PAD), and investment on the GRDP of Bali Province. The research utilizes secondary data from nine regencies/cities in Bali over a six-year period (2018–2023). Data analysis is conducted using panel data regression with the Eviews 12 software. The results indicate that tourist visits, PAD, and investment collectively influence the GRDP of Bali Province. Partially, tourist visits and PAD have a positive and significant impact on GRDP, while investment has a negative but insignificant effect. The findings suggest that optimizing tourism potential, improving infrastructure, maximizing the potential of each region to increase local revenue, and exploring investment opportunities beyond the tourism sector—while supporting both domestic and foreign investment are essential to boosting Bali’s GRDP.